การพัฒนาตัวบ่งชี้ความกล้าหาญทางจริยธรรมของครู : การทดสอบความไม่แปรเปลี่ยนของการวัดตามภูมิหลังของครู - พักตร์วิภา หน่อสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this research were; 1) to develop moral courage indicators of teachers, 2) to investigate the correspondence of indicators of moral courage for teacher model, and 3) to test measurement invariance of the model of moral courage indicators of teachers across backgroups. Methodology was divided into three phases; 1) document analysis, 2) collection of qualitative data from interviewing teachers, and 3) data collection by questionnaires. The participants of this research were 778 teachers under The Basic Education Commission. The research instruments were moral courage’s interview form and teacher’s moral courage questionnaires. The collected data was analyzed through descriptive statistics, second order confirmatory analysis, and multi-group structural equation analysis by LISREL program. The research findings were: 1) Moral courage indicators of teachers consisted of four factors, namely moral principle, moral situation, moral behavior and endurance of threats. The factors consisted of 11 indicators: honesty, respect, responsibility, fairness, compassion, assess situation, scan values, contemplate dangers, talking, action and endure. 2) The model of moral courage indicators for teachers found that the model fit the empirical data. ( χ² = 13.129, df = 20, p = 0.872, GFI = 0.997, AGFI = 0.990 and RMSEA = 0.000) 3) The model of moral courage indicators for teachers indicated invariance of model form between male and female teachers and between size of school, but the model indicated variance of the factor loading of each indicators and factor loading of moral principle moral situation moral behavior and endurance of threats to research factors.